A 7‐day high‐fat, high‐calorie diet induces fibre‐specific increases in intramuscular triglyceride and perilipin protein expression in human skeletal muscle. (14th February 2020) - Whytock, K. L.; Parry, S. A.; Turner, M. C.; Woods, R. M.; James, L. J.; Ferguson, R. A.; Ståhlman, M.; Borén, J.; Strauss, J. A.; Cocks, M.; Wagenmakers, A. J. M.; Hulston, C. J.; et al.
Abstract : Key points: We have recently shown that a high‐fat, high‐calorie (HFHC) diet decreases whole body glucose clearance without impairing skeletal muscle insulin signalling, in healthy lean individuals. These diets are also known to increase skeletal muscle IMTG stores, but the effect on lipid metabolites leading to skeletal muscle insulin resistance has not been investigated. This study measured the effect of 7 days' HFHC diet on (1) skeletal muscle concentration of lipid metabolites, and (2) potential changes in the perilipin (PLIN) content of the lipid droplets storing intramuscular triglyceride (IMTG). The HFHC diet increased PLIN3 protein expression and redistributed PLIN2 to lipid droplet stores in type I fibres. The HFHC diet increased IMTG content in type I fibres, while lipid metabolite concentrations remained the same. The data suggest that the increases in IMTG stores assists in reducing the accumulation of lipid metabolites known to contribute to skeletal muscle insulin resistance. Abstract: A high‐fat, high‐calorie (HFHC) diet reduces whole body glucose clearance without impairing skeletal muscle insulin signalling in healthy lean individuals. HFHC diets also increase skeletal muscle lipid stores. However, unlike certain lipid metabolites, intramuscular triglyceride (IMTG) stored within lipid droplets (LDs) does not directly contribute to skeletal muscle insulin resistance. Increased expression of perilipin (PLIN) proteins and colocalisation to LDs has been shown to assist in IMTG storage. We aimed to test the hypothesis that 7 days on a HFHC diet increases IMTG content while minimising accumulation of lipid metabolites known to disrupt skeletal muscle insulin signalling in sedentary and obese individuals. We also aimed to identify changes in expression and subcellular distribution of proteins involved in IMTG storage. Muscle biopsies were obtained from the m. vastus lateralis of 13 (11 males, 2 females) healthy lean individuals (age: 23 ± 2.5 years; body mass index: 24.5 ± 2.4 kg m −2 ), following an overnight fast, before and after consuming a high‐fat (64% energy), high‐calorie (+47% kcal) diet for 7 days. After the HFHC diet, IMTG content increased in type I fibres only (+101%; P < 0.001), whereas there was no change in the concentration of either total diacylglycerol ( P = 0.123) or total ceramides ( P = 0.150). Of the PLINs investigated, only PLIN3 content increased (+50%; P < 0.01) solely in type I fibres. LDs labelled with PLIN2 increased (+80%; P < 0.01), also in type I fibres only. We propose that these adaptations of LDs support IMTG storage and minimise accumulation of lipid metabolites to protect skeletal muscle insulin signalling following 7 days' HFHC diet. Key points: We have recently shown that a high‐fat, high‐calorie (HFHC) diet decreases whole body glucose clearance without impairing skeletal muscle insulin signalling, in healthy lean individuals. These diets are also known to increase skeletal muscle IMTG stores, but the effect on lipid metabolites leading to skeletal muscle insulin resistance has not been investigated. This study measured the effect of 7 days' HFHC diet on (1) skeletal muscle concentration of lipid metabolites, and (2) potential changes in the perilipin (PLIN) content of the lipid droplets storing intramuscular triglyceride (IMTG). The HFHC diet increased PLIN3 protein expression and redistributed PLIN2 to lipid droplet stores in type I fibres. The HFHC diet increased IMTG content in type I fibres, while lipid metabolite concentrations remained the same. The data suggest that the increases in IMTG stores assists in reducing the accumulation of lipid metabolites known to contribute to skeletal muscle insulin resistance.